Expert System for Diagnosing Pests and Diseases on Onion Crops due to Climate Change and Weather using Bayes' Theorem Method - Adam Jordan Lumbangaol (International Journal of Basic and Applied Science, 2020)
The main purpose of this study is to diagnose the types of pests and diseases on shallot plants due to climate change and weather carried out at the Department of Agriculture, Humbang Hasundutan district. Pests and diseases of shallot plants can be disturbed or infected by pests and diseases to other shallot plants so that farmers need to be wary of. Therefore, the dissemination of information about pests and diseases is very necessary to find out early on the types of pests and diseases in shallot plants due to climate and weather changes. Types of pests and diseases of shallots due to climate and weather changes are onion caterpillar (Spodoptera exiqua), leaf miner fly (Liriomyza chinensis), bodas pest (Thrips tabaci), purple spot (Alternaria porri), anthracnose (Cholletorichum gloesprorioiodes), dew , Mosaic disease or mole. So that it aims to produce an application-based expert system to diagnose pests and diseases on shallot plants due to climate and weather changes through the symptoms that occur in shallot plants. The methodology used for this research is the Bayes Theorem method. References from internet books and experts in their fields are Sumurung Toga Torop, who works at the Humbang Hasundutan Agriculture Service. As for the software using Visual Basic 2010 as its programming language, as well as Microsoft Access 2010.